(untitled) (Community Based Medical Journal, 2013)
Fibrous dysplasia is an idiopathic developmental bone disease of benign origin that has been linked to a localized developmental arrest; all of the components of normal bone are present but they do not differentiate into their mature structures. It causes skeletal deformity & pathological fracture of bone. The lesion appear in three distinctive but sometimes overlapping clinical pattern 1.single bone involvement(monostotic);2.multiple bone involvement (polyostotic);and 3. polystotyic disease, associated with cafe-au-lait skin pigmentation and endocrine abnormalities, especially precocious puberty. The study was done in CBMCB hospital. The patient came to us with a swelling in the left side of check and a mass in left nasal cavity. Biopsy was taken from nasal mass which revealed fibrous dysplasia. Later on, surgical intervention was done by lateral rhinotomy approach. Post operative period was uneven full and patient was discharged on 7th POD. After four weeks interval, follow up revealed no deformity in check .No nasal obstruction was found and scar mark was also reasonable. DOI: http://dx.doi.org/10.3329/cbmj.v1i1.13843 Community Based Medical Journal Vol.1(1) 2012 27-29